Naked Censorship: Stripping the Censors’ Discourse - Anne Etienne (Revue LISA)
Feared for its subversive potential, the English stage was subjected to the pre-production control exercised by the Lord Chamberlain for over 200 years. This inter-disciplinary paper aims to shed light on the principles that led to the establishment of theatre censorship legislation and the politics of inertia of the ensuing governments, hence offering an alternative perspective to the moral argument first utilised by Walpole and later forwarded as a final defence. In doing so, we will explore the gap between the censors’ procedures and their discourses, thereby gaining an insight into the means and hidden dynamics of this disciplinary control. This will allow us to gauge how (rapidly) different censors have adapted to internal (i.e. governmental) and external (i.e. theatrical) pressure and how these changes have affected the relationship between authors and censors. Finally, we shall question the remaining existence of censorship in the post-1968 period.The paper is based on archival research carried out at the British Library (Lord Chamberlain’s manuscript collection), the National Archives (governmental papers) and on interviews with authors and theatre practitioners.